Addition of Kecombrang Flower Flour (Etlingera elatior) to the Characteristics of Red Beans Noodles - Marcliansi Sinaga; Marniza Marniza; Lukman Hidayat (Badan Penerbitan Fakultas Pertanian (BPFP), 2022)
Along with the times, many types of food have changed both in terms of taste, appearance, and presentation. One of the foods that are much favored by the community and easy to serve is wet noodles. Wet noodles supplemented with 10% red bean flour is expected to help fulfill protein. Moisture content of wet noodles reaches 52% so that the shelf life is quite short. Kecombrang can be used as a preservative to extend the shelf life of wet noodles. This research was conducted to obtain physical, chemical, organoleptic and shelf life characteristics based on the Total Plate Count (TPC) of red bean wet noodles. The experimental design used in this study was a single factor Randomized Block Design (RAK), namely the addition of kecombrang flower flour with 5 treatment levels, namely 1%, 2%, 3%, 4% and 5%, from 100 g flour (90 g wheat flour + 10 g red bean flour). Each treatment was repeated 3 times to obtain 15 experimental units. The results showed that the highest water content was 64,33%, the brightest color was in the 1% treatment with a value of 5Y 9/3, while the darkest color was in the 5% treatment with a value of 5Y 7/2, the highest texture was 37,78 mm/g/ s, the highest protein was 14,09%, the highest ash content was 1,17%, the concentration of addition of 5% kecombrang flower flour was able to extend the shelf life of red bean wet noodles for 48 hours, organoleptic characteristics showed that the panelist acceptance rate was at a concentration of 1% - 3 % based on the overall rating. Keywords: Kecombrang, Red beans, Shelf life, Wet Noodles.